ANALISIS FAKTOR UPAH DAN MODAL TERHADAP PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI KECIL MENENGAH KENDANG JIMBE KOTA BLITAR - Muhammad Yusuf Hanafi; Aris Soelistyo; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2020)
Labor absorption is the large number of workers absorbed or working in a business or company. Increased employment will affect wages and capital. This writing has the aim to determine the effect of wages and capital on employment. The data analysis method used is multiple regression analysis on cross-section data to determine the effect of independent variables with the dependent variable. The first step in conducting regression is to test through the classical assumption test, including the normality test, the multicollinearity test, the heteroscedasticity, and autocorrelation test, and the statistical analysis of regression analysis. The results of the hypothesis proposed in this study, the two variables significantly influence the dependent variable. The wage variable has a significant and positive effect on labor absorption in Kendang Jimbe small and medium industries in Blitar City, capital variables have a significant and positive effect on labor absorption in Kendang Jimbe small and medium industries in Blitar City.